Correlation of Anti-Salmonella Antibodies Between Serum and Saliva Samples Collected From Finisher Pigs - De Lucia, Alessia; Cawthraw, Shaun; Davies, Rob; Smith, Richard P.; Bianco, Carlo; Ostanello, Fabio; Martelli, Francesca (Frontiers in Veterinary Science, 2020)
Saliva and oral fluids (OF), obtained by using absorptive devices, can provide an alternative diagnostic matrix to serum for monitoring disease status in pigs. The aim of this study was to investigate the correlation of anti-Salmonella antibodies between serum and saliva samples collected from pigs. Individual paired serum and saliva samples were collected from five pigs housed in four pens, and pooled OF was collected using a cotton rope in the same pens. Pooled serum and saliva samples were created by pooling five individual samples from each pen. Salmonella IgG was detected in individual/pooled serum samples using a commercial Salmonella ELISA kit, validated for sera. The same kit was used with a protocol modified by extending incubation time and increasing temperature to test individual/pooled saliva and OF samples. Anti-Salmonella IgG antibodies in pig saliva were always detected at a lower level than in the matching serum samples. A significant correlation (p=0.002) and a substantial agreement (k>0.66 p=0.002) was found between individual Salmonella IgG in serum and saliva samples, and a positive agreement was found between the four pools of saliva and serum. Pen-based OFs were ELISA-positive when collected from pens that had a high Salmonella seroprevalence. The size of this investigation was small, and further studies are necessary to further confirm these findings. The results of this work provide some evidence that saliva samples have the potential to be used for the diagnosis of Salmonella infection in pig farms.